Product Competitiveness and Market Penetration in South Sulawesi: Mapping of Leading Export Commodities - Indraswati Tri Abdi Reviane; Abdul Hamid Paddu; Muhammad Jibril Tajibu (Hasanuddin Economics and Business Review, 2022)
This study analyzes the competitiveness and market penetration of the leading export commodities of South Sulawesi. The Klassen typology and Export Product Dynamic method used to map the leading export commodities based on the competitiveness, market penetration power, and export dynamic of each commodity. This study focuses on measuring competitiveness and market penetration of each leading export commodity by using the "Revealed Comparative Advantage" and "Index of Export Market Penetration" indicators.This study also aims to analyze the determinants of competitiveness and market penetration of these leading export commodities, as well as their ability to encourage increased economic prosperity and create an effective and harmonious business environment in South Sulawesi.This study found that are Nickel, Lac, Fish, and Cocoa are leading export commodities of South Sulawesi which have very strong competitiveness and high market penetration. Meanwhile, the leading export commodities of South Sulawesi which have very strong competitiveness but moderate market penetration are Salt, then commodities have strong competitiveness and moderate market penetration are Coffee, Preparations of Meat and Fish, and Residues from food industries. Furthermore, Fruits; Oil Seeds; and Sugars are commodity that have strong competitiveness but low market penetration. There are six commodities in rising star position and five commodities in a loss opportunity position.